Kebijakan Dividen Antara Efek Syariah Dengan Efek Konvensional - Salis Musta Ani; Hotman Fredy (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2014)
This study aims to reveal the dividend policy of the companies listed in the Islamic Securities and Exchange Conventional in 2012 in Indonesia Stock Exchange through a comparison of the two types of these securities in testing the effect of the current ratio (CR), cash position (CP), and the debt equity ratio (DER ), and net profit margin (NPM) on dividend policy by proxy dividend payout ratio (DPR). Growth (GROWTH) and firm size (SIZE) becomes the controlling variable in this study. Using data from 64 companies listed on the Stock Exchange DER result that significant positive effect on the DPR for Islamic securities. While the growth control variables proved significant negative effect on the DPR for Islamic securities. To test the model 2 (DPRK) obtained the result that the profitability (NPM) and the size effect on the DPR to conventional effects. This test illustrates that dividends on both the effects of development policy, is significantly affected by different variables. This is likely because the decision for investment or other financing different in each category effects. Moreover, we can see that the average dividend policy on Islamic securities is higher than the average dividend policy on conventional effects. This result could increase investor interest in the shares of sharia and encourage the development of Islamic securities. However, there are things that need attention, ie companies with Islamic securities need to further improve profitability.